2020
DOI: 10.1371/journal.pone.0229910
|View full text |Cite
|
Sign up to set email alerts
|

Innovating within or outside dominant food systems? Different challenges for contrasting crop diversification strategies in Europe

Abstract: Innovations supporting a shift towards more sustainable food systems can be developed within the dominant food system regime or in alternative niches. No study has compared the challenges faced in each context. This paper, based on an analysis of 25 cases of European innovations that support crop diversification, explores the extent to which barriers to crop diversification can be related to the proximity of innovation settings with dominant food systems. Drawing on a qualitative analysis of interviews and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 50 publications
1
79
0
2
Order By: Relevance
“…Importantly, this study showed that in addition to market opportunities and supportive policies, a key factor driving the stable introduction of legumes on farms was increased knowledge and awareness of their multiple and longterm agroecological benefits, i.e., the ES that they can deliver. Similarly, a comprehensive study on barriers to crop diversification in general found that "convincing" conventional farmers in Europe to adopt more agroecological practices, such as including legumes in rotations, would require providing them with more evidence of the positive relationship between crop diversification and the sustainability of their farms (Morel et al 2020). Additionally, Zimmer et al (2016) surveyed Luxembourgish farmers and found the majority to be under-informed about legume cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, this study showed that in addition to market opportunities and supportive policies, a key factor driving the stable introduction of legumes on farms was increased knowledge and awareness of their multiple and longterm agroecological benefits, i.e., the ES that they can deliver. Similarly, a comprehensive study on barriers to crop diversification in general found that "convincing" conventional farmers in Europe to adopt more agroecological practices, such as including legumes in rotations, would require providing them with more evidence of the positive relationship between crop diversification and the sustainability of their farms (Morel et al 2020). Additionally, Zimmer et al (2016) surveyed Luxembourgish farmers and found the majority to be under-informed about legume cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…The first phase of the co-innovation approach was to involve the CS actors in the identification of the challenges they face. Barriers to organic hemp development in Sicily were characterised based on a qualitative and iterative inquiry procedure detailed in Morel et al (2020). This approach can be briefly summarised by the following steps: in January 2018, a two-hour brainstorming was carried out with the CS team using the causal analysis method to realize an initial problem tree (Van Mierlo et al, 2010;AUSAID, 2005) for defining the main barriers related to organic hemp.…”
Section: Characterisation Of Barriers To Organic Hemp Development In mentioning
confidence: 99%
“…It aimed at structuring all the material and knowledge informally collected by the CS team during their prior interactions with CS actors; this first overview of barriers was enriched by complementary one-hour semi-structured interviews led by the CS team with the CS actors (the CS hemp growers). Those interviews were carried out based on a set of topics and a structured data collection framework shared across DiverIMPACTS CSs (Morel et al, 2020) ensuring that all levels of the value chain were covered: (i) farmers and production, (ii) downstream operations from farm to retailing, (iii) marketing and consumers, (iv) contracts and coordination between actors; all the collected data were processed progressively through a method of qualitative analysis (Elo and Kyngäs, 2008) using the coding and matrix tools described by Miles and Huberman (1984). The general aim of this approach was to gradually organise the information gathered by the Sicilian CS team through discussions with the different value chain stakeholders along the co-innovation dynamic in a perspective of learning by doing.…”
Section: Characterisation Of Barriers To Organic Hemp Development In mentioning
confidence: 99%
See 1 more Smart Citation
“…There is therefore increasing interest in exploring new sources of genetic variation (Castañeda‐Álvarez et al., 2016; Smýkal et al., 2018). For example, there may be the potential for significant gains in yield and quality in under‐utilized species that have not yet been subject to scientific breeding or genetic analysis, and which might mitigate the pressures on existing major crops (Castañeda‐Álvarez et al., 2016; Pironon et al., 2019; Zhang, Li, & Zhu, 2018) if the sociological barriers to their use can be overcome (Morel, Revoyron, San Cristobal, & Baret, 2020).…”
Section: Introductionmentioning
confidence: 99%